MATRIMONIAL RIGHTS AND THE EXPECTATIONS RELATED TO MARRIAGE IN NEWSPAPER ADS BY THE END OF THE 19TH AND EARLY 20TH CENTURIES IN CROATIA - Lachner, Višnja; Kordić, Ljubica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The authors explore the social and legal status of unmarried women and social rules and customs affecting their behavior related to marriage and the relationship between men and women in the 19th and early 20th centuries in Croatia, which was then a part of the Austrian Empire i.e. Austro-Hungarian Monarchy. The research is founded on two different corpora. The first encompasses relevant legal acts regulating marriage at that time, including special rules for royal soldiers regarding their rights to get married. The second part of the research is founded on newspaper announcements, specifically: matrimonial and contact ads, in which men and women express their wish to meet a potential spouse or lover. The corpus of ads is excerpted from the local newspapers of Osijek Die Drau and Slavonische Presse that were published in the German language in the explored historical period. The issues of both newspapers published between 1870 and 1938 are available in digitalized versions. Matrimonial and contact ads by men and women as potential spouses or love couples represent a valuable source of information about social rules and customs related to marriage and the relationship between men and women when social communication and social media were very limited. The paper aims to present legal rules regulating men’s and women’s rights and duties relating to marriage but also to shed light on how communication between potential love partners or spouses through printed media influenced the social position and identity of women by analyzing relevant newspaper ads from legal, socio-psychological, and socio-linguistic points of view
Keywords: legal aspect; social rules; love and marriage; newspaper ads; Croatia.